2019
DOI: 10.1155/2019/2691514
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-25 Protects Smooth Muscle Cells against Corticosterone-Induced Apoptosis

Abstract: Background and Aims. Vascular smooth muscle cells (VSMCs) are central components of atherosclerotic plaque. Loss of VSMCs through apoptotic cell death can cause fibrous cap thinning, necrotic core formation, and calcification that may destabilize plaque. Elevated glucocorticoid levels caused by psychological stress promote VSMC apoptosis and can exacerbate atherosclerosis in mice and humans. Changes in the levels of antiapoptosis microRNA-25 (miR-25) have been linked with heart disease, inflammation, VSMC phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Measurement of ROS. ROS were measured using an Oxi-Select ROS assay kit, exactly as described by the manufacturer and as previously reported [64].…”
mentioning
confidence: 99%
“…Measurement of ROS. ROS were measured using an Oxi-Select ROS assay kit, exactly as described by the manufacturer and as previously reported [64].…”
mentioning
confidence: 99%
“…Furthermore, miR-25 can inhibit corticosterone-induced VSMC apoptosis by targeting the pro-apoptotic protein MOAP1 and possibly also the p70S6k pathway [ 305 ]. MOAP1 promotes caspase-dependent apoptosis by binding pro-apoptotic BAX via its Bcl-2 homology-3- (BH3-) like domain, and it is up-regulated upon several apoptotic stimuli [ 306 ].…”
Section: Apoptosis and Vascular Calcificationmentioning
confidence: 99%
“…MOAP1 promotes caspase-dependent apoptosis by binding pro-apoptotic BAX via its Bcl-2 homology-3- (BH3-) like domain, and it is up-regulated upon several apoptotic stimuli [ 306 ]. Since MOAP is a direct target for miR-25, it has been suggested that miR-25-dependent down-regulation of MOAP1 may represent a key mechanism in apoptosis inhibition with positive effects on atherogenesis and eventually on calcification [ 305 ]. It has to be further investigated if these data may also be relevant for therapeutic implications in humans.…”
Section: Apoptosis and Vascular Calcificationmentioning
confidence: 99%
“…MiR-25, also an onco-miR, was reported to interfere with calcium handling, attenuate inflammation, and decreased apoptosis in myocardial and renal tissues [87]. Zhang and colleagues showed that in mouse VSMCs, over-expression of miR-25 could ameliorate exogenous stimuli-triggered apoptosis and potentially subsequent calcification [51]. MiR-26a plays a pivotal role in different types of cancers by regulating cellular proliferation and participates in cardiovascular pathophysiology by targeting glycogen synthase kinase (GSK)-3β, a Wnt/β-catenin pathway component [88].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 99%